HUBUNGAN ANTARA KELELAHAN KERJA DENGAN STRES KERJA PADA PEKERJA PROYEK PEMBANGUNAN 6 RUAS TOL DALAM KOTA SEKSI 1A KSO JAYA KONSTRUKSI-ADHI TAHUN 2021 - Ilhamsyah Mulyadi, (2021)
Construction activities in Indonesia are one of the places that can potentially trigger fatigue and result in work stress. Fatigue can reduce the ability to work which is characterized by a decrease in activity. A balance, on physical work can make workers comfortable, safe, and not experience excessive work-related stress. The purpose of this study was to determine the association between work fatigue and work-related stress among construction workers of Intra-City Highway Construction Project Jaya Konstruksi-Adhi. This was a quantitative study with cross-sectional design. The sample were 120 workers and selected using the accidental sampling technique. The results from the bivariate analysis showed that there was associations between work fatigue (p = 0.001), work duration (p = 0.007), and years of service (p = 0.009) with work-related stress. Therefore, workers are advised to optimize rest time, multiply, drink water and stretch muscles between work and companies must be able to identify workers who have difficulties in managing sources of work stress so that they are immediately addressed.